2013
DOI: 10.1039/c3fo30317a
|View full text |Cite
|
Sign up to set email alerts
|

The role of antioxidants and other agents in alleviating hyperglycemia mediated oxidative stress and injury in liver

Abstract: Several antioxidants and agents having similar antioxidant effects are known to exert beneficial effects in ameliorating the injurious effects of hyperglycemia on liver in different diabetic in vitro and in vivo models. The review deals with some of the agents which have been shown to exert protective effects on liver against hyperglycemic insult and the various mechanisms involved. The different classes of agents which protect the diabetic liver or decrease the severity of hyperglycemia mediated injury includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 200 publications
(723 reference statements)
4
90
0
1
Order By: Relevance
“…With regard to the latter, green tea catechins were demonstrated to decrease glucose levels and to increase glucose tolerance in insulinresistant mice [25]. EGCG attenuated dexamethasone and TNF-α promoted ROS generation and increased glucose uptake ability in this study [25], congruent with concepts that catechins are mainly acting through their antioxidative properties [26,27]. However, there are also reports suggesting that other mechanisms, including direct interactions with plasma membrane proteins, regulation of signal transduction pathways or mitochondrial function, might be more important in order to exert many of its beneficial biological actions [28].…”
Section: Discussionsupporting
confidence: 85%
“…With regard to the latter, green tea catechins were demonstrated to decrease glucose levels and to increase glucose tolerance in insulinresistant mice [25]. EGCG attenuated dexamethasone and TNF-α promoted ROS generation and increased glucose uptake ability in this study [25], congruent with concepts that catechins are mainly acting through their antioxidative properties [26,27]. However, there are also reports suggesting that other mechanisms, including direct interactions with plasma membrane proteins, regulation of signal transduction pathways or mitochondrial function, might be more important in order to exert many of its beneficial biological actions [28].…”
Section: Discussionsupporting
confidence: 85%
“…These results are consistent with previous researches2526, indicating that iAs can increase the hepatic toxicity. In db/db control mice, these genes were also up-regulated in liver and adipocyte, indicating that diabetes can also cause oxidative damage and inflammation2728. iAs exposure further increased oxidative damage and inflammation, and worsened hepatotoxicity in diabetic individual.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the ability of the extract to regulate oxidative stress in these tissues may have played a role in the regulation of sorbitol. It has been demonstrated that increased oxidative stress propagates the buildup of sorbitol and other complications in Type 2 diabetes (Dey & Lakshmanan 2013;Rahimi et al 2005) and the results from this study showed that the untreated diabetic control group had lower antioxidant capacities in the lens, kidney and nerve (Table 2), while the R. cinerea-treated groups had improved antioxidant capacities, although only those of the kidney were significant different (p<0.05).…”
Section: R Cinerea Improved Lipid Profiles Oxidative Stress and LImentioning
confidence: 57%